P046 A review and retrospective case series of paediatric Sjögren's syndrome from Southern Africa. (11th November 2021) - Akhalwaya, S Y; Webb, K; Scott, C
Abstract: Background: Paediatric Sjögren's syndrome (pSS) is an uncommon autoimmune paediatric disease, rarely reported in children in Africa. It remains an important consideration in a child with parotid swelling. Here, we present a retrospective case-series of four patients from a paediatric rheumatology clinic in South Africa and discuss some of the difficulties of diagnosis in our context. Methods: We performed a retrospective analysis of patients who attend the Red Cross War Memorial Hospital Paediatric Rheumatology clinic between 2010 and 2019. Result: The four patients diagnosed with Sjögren's all had varied presentations and disease courses. There were 3 females and 1 male and the ages at diagnosis ranged from 6 to 19 years old. The time to diagnosis was prolonged and ranged from 1 month to 10 years. Two patients with primary pSS presented with extra-articular manifestations of arthritis, abdominal pain and fatigue, followed by dry mouth, dry eyes, parotid swelling and and suggestive histopathology. The remaining 2 patients had a secondary pSS due to juvenile onset SLE and tuberculosis respectively. Conclusion: In less resourced settings the diagnosis of pSS is often delayed. Both patients with primary pSS had preceding extra-glandular manifestations. In less resourced settings, infectious diseases may present as pSS and associated rheumatic diseases causing secondary pSS must be considered.